Environmental fate of pesticides used as seed dressing - Kuhlau, Åsa (2008)
Residues of chemical substances contained in pesticides (plant protection products) have been found in streams in four agricultural areas in Sweden despite no reported direct use. This report investigated whether these residues originated from seed dressing preparations used in the areas or some other source. Nine substances, two insecticides and seven fungicides included in the Swedish Pesticide Monitoring Programme, were investigated.